2009
DOI: 10.1093/nar/gkp107
|View full text |Cite
|
Sign up to set email alerts
|

Distinct GDP/GTP bound states of the tandem G-domains of EngA regulate ribosome binding

Abstract: EngA, a unique GTPase containing a KH-domain preceded by two consecutive G-domains, displays distinct nucleotide binding and hydrolysis activities. So far, Escherichia coli EngA is reported to bind the 50S ribosomal subunit in the guanosine-5′-trihosphate (GTP) bound state. Here, for the first time, using mutations that allow isolating the activities of the two G-domains, GD1 and GD2, we show that apart from 50S, EngA also binds the 30S and 70S subunits. We identify that the key requirement for any EngA–riboso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 30 publications
6
54
2
Order By: Relevance
“…The engA gene upstream of B. cenocepacia J2315 hfq is not found in the E. coli hfq locus. In E. coli, the genes immediately upstream of hfq are miaA-mutL-amiB (Tsui et al, 1994 of two GTP-binding domains arranged in tandem which binds to the ribosome subunits 50S, 70S and 30S, and participates in ribosome biogenesis (Tomar et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The engA gene upstream of B. cenocepacia J2315 hfq is not found in the E. coli hfq locus. In E. coli, the genes immediately upstream of hfq are miaA-mutL-amiB (Tsui et al, 1994 of two GTP-binding domains arranged in tandem which binds to the ribosome subunits 50S, 70S and 30S, and participates in ribosome biogenesis (Tomar et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…EngA is a broadly conserved bacterial GTPase with two GTP binding domains and is likely involved in ribosome biogenesis (59). S. meliloti engA is located 122 nt downstream of smb20996, and results from plasmid integration experiments strongly suggest that engA is transcribed from a promoter that lies upstream of smb20996 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9 GTP binds to Der in a cooperative manner and the interruption of cooperative nucleotide association disrupts the interaction of Der with the 50S subunit. 11,12,15,16 The essential role of Der in 50S subunit assembly was further supported by the isolation of Der as a suppressor for the rrmJ null phenotype. 17 RrmJ is a 23S ribosomal RNA methyltransferase and its deletion resulted in reduction of the functional 70S ribosomes and accumulation of 30S and 50S subunits.…”
Section: Introductionmentioning
confidence: 94%
“…13,14 In case of T. maritima Der, each of the two Der GTP-binding domains expressed separately has an intrinsic GTPase activity, though the activity of the N-terminal GD1 domain is stronger than that of the GD2 domain. 13 It has been demonstrated that Der has a critical role in 50S subunit biogenesis, as it associates with 50S subunit in the presence of a GTP analog 9,15 and its depletion caused conformational instability of 50S subunit at a low Mg 2+ concentration. 9 GTP binds to Der in a cooperative manner and the interruption of cooperative nucleotide association disrupts the interaction of Der with the 50S subunit.…”
Section: Introductionmentioning
confidence: 99%